Northwest history. Mining. Report. 1920-08-21 (1920)
Lead replaces zinc showing in friend mine. - William Schierding, manager of the Friend Mining company on Beaver creek, in the Coeur d'ALenes, returned this week form the property and reports lead taking the place of zinc in the drift from the 50-foot shaft.